Educational opportunities for the emerging corona crisis (COVID-19) from the point of view of the female students of the Faculty of Education at the Islamic University - أ.د/ صلاح الناقة; د/ أحمد اسعيفان الصوراني; د/ خالد غانم العطار (Taez University, 2022)
This study aimed toinvestigate the educational opportunities for the emerging corona crisis      (COVID-19) from the point of view of the female students of the faculty of education at the Islamic University, To achieve the aims of the study, the researchers used the descriptive analytical approach, The sample of the study consisted of (146) female students of the College of Education at the Islamic University, The researchers also designed a questionnaire consisting of (18) items to achieve the objectives of the study, divided into three domains (the first domain: educational opportunities, the second domain: social opportunities and the third domain: cultural opportunities). The study reached the following results:      The educational field obtained a relative weight (63.42%), i.e. with a medium degree of appreciation, while the social field obtained a relative weight (62.79%), i.e. with a medium degree of appreciation, while the cultural field obtained a relative weight (68.49%) to a large degree, in addition to the students acquiring new skills in Learning through modern e-learning platforms, In addition to an increase in awareness by learning about the cultures of other societies to benefit from their experiences.      Based upon the previous findings, the researchers recommend the need to take advantage of the educational opportunities of the Corona crisis in their practical and scientific lives, and the researchers also recommend the need to study the opportunities for each crisis in order to reduce the negative effects of this pandemic on learning, education, social and cultural life.